Collateral and Repeated Lending - Artashes Karapetyan; Bogdan Stacescu (Norges Bank, 2012)
Lending is often associated with significant asymmetric information issues between suppliers of funds and their potential borrowers. Banks can screen their borrowers, or can require them to post collateral in order to select creditworthy projects. We find that the potential for longer-term relationships increases banks' preference for screening. This is because posting collateral only provides the information that the current project of a given borrower is of good quality, whereas screening provides information that can be used in evaluating future projects as well as the current ones.
hdl:11250/2496818
Keywords: G21; L13; 330; collateral; screening; bank relationships